2019
DOI: 10.32098/mltj.01.2016.02
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the cellular origin of rotator cuff muscle fatty infiltration and fibrosis after injury

Abstract: Background: rotator cuff muscle atrophy, fibrosis and fatty infiltration are common complications after large and massive rotator cuff tears. Currently, there are no effective treatments for these muscle pathologies after injury. Furthermore, the cellular source for fibrotic and adipose tissues in rotator cuff muscle after injury remains unknown. In this study, we proposed that two groups of muscle resident progenitors, Tie2+ muscle mesenchymal progenitors and PDGFRα + fibro/adipogenic progenitor cells (FAPs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Rowshan et al 39 noted, in a rabbit animal study, that tendon tenotomy and nerve transection lead to similar patterns of fatty accumulation. Supporting this work, several studies using mice have found similar evidence to link rotator cuff tears and neuropathic muscle atrophy 40-44 . As was the case in our study, Rowshan et al noted that muscles in their group with a partial rotator cuff tear did not display evidence of increased fatty accumulation 39 .…”
Section: Discussionsupporting
confidence: 67%
“…Rowshan et al 39 noted, in a rabbit animal study, that tendon tenotomy and nerve transection lead to similar patterns of fatty accumulation. Supporting this work, several studies using mice have found similar evidence to link rotator cuff tears and neuropathic muscle atrophy 40-44 . As was the case in our study, Rowshan et al noted that muscles in their group with a partial rotator cuff tear did not display evidence of increased fatty accumulation 39 .…”
Section: Discussionsupporting
confidence: 67%
“…Another massive rotator cuff tear model caused by a full-thickness tenectomy of the right supraspinatus and infraspinatus in rats showed that the muscle fiber force is decreased and expressions of fibrosis and lipid accumulation related genes were increased [21]. A further study performed by Liu et al demonstrated that the main cellular sources involved in fatty infiltration were Tie2 + progenitor cells and fibro/adipogenic progenitor cells [22]. These three studies were consistent with the clinical reports and researches.…”
Section: Discussionsupporting
confidence: 67%
“…The degree of fatty infiltration can be assessed by computerised tomography (CT) scan, magnetic resonance imaging (MRI) and ultrasound [120]. The origin of fatty infiltration is largely thought to be through adipocyte differentiation of the PDGFRα( +) fibro/adipogenic progenitor cells (FAPs) residing in muscle [121]. However, fatty infiltration seems to progress from MTJ into muscle after tendon injury, raising the possibility that the signals or cells from tendon may contribute to fatty infiltration in MTJ and/or muscles [122] (Fig.…”
Section: Aberrant Differentiation Of Tendon Cells In Tendinopathymentioning
confidence: 99%